Poverty-Reducing or Poverty-Inducing? A CGE-based Analysis of Foreign Capital Inflows in Pakistan - Rizwana Siddiqui; A. R. Kemal (NUST Journal of Social Sciences and Humanities, 2021)
Foreign capital inflows (FKI) help an economy by financing the imbalance between income and expenditure. However, their impact on poverty in the recipient economy is a controversial issue. In this study, a static computable general equilibrium (CGE) model for Pakistan has been used to assess the impact of foreign capital on poverty. Several interesting results emerged from the study. FKI increase demand for goods for investment purposes that lead to the expansion of import-competing- sector machinery to fulfil domestic demand. However, the contraction of the majority of trading sectors combined with expansion of non-trading sectors of the economy have generated ‘Dutch disease effect’. The results show that FKI have a positive impact on poverty in Pakistan. Trade liberalization of import of machinery reduces the negative effect of the decline in FKI. Rise in poverty in Pakistan may be attributed to the decline in foreign capital.